Issues and Challenges of English Language Teacher-Trainees’ Teaching Practicum Performance: Looking Back and Going Forward - Deocampo, Marilyn Fernandez (LEARN Journal: Language Education and Acquisition Research Network, 2020)
To become a better teacher, teachers are encouraged to practice ‘a reflective mind’ to have an insight of what is going on in the classroom and decipher what works and would not work (Farrell, 2018). Teachers, the English language teachers in particular, are likely to face many challenges not only in the global economy and competitive market of English education but also to the demanding nature of a teaching career. So, this study is intended to help identify the issues and challenges encountered by 15 teacher-trainees’ who undertook their teaching practicum. The narrative inquiry approach was used to identify the issues and challenges of their teaching performance. Using convenience sampling in choosing the samples, reflection papers and semi-structured interviews were used as the instruments to collect data. The findings indicated that, teacher’s voice, classroom management, teaching strategies, learning strategies, English communication barriers, vocabulary knowledge, lesson planning, teaching appraisal and classroom motivation were among the issues and challenges the trainees encountered. The indication is that, by looking back, teacher-trainees would understand the essence of a good language (English) teacher, as well as, to reflect, self-critique, assess and improve part of their teaching. Being aware of the issues and challenges in a real teaching environment can shape teacher-trainees personal and professional growth and can be a good resource for going forward and to be successful in their teaching profession